Development of the Wind Direction Indicator Display as a Learning Media for Visual Landing Aid Systems - Soleh, Asep Muhamad; Sukahir, Sukahir; Widiarto, Hendro; Kusumastuti, Mayang Enggar; Nugroho, Fachregi; Alddi, Muhammad Dimas Bara (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
In this study, we designed a wind direction indicator display as a learning medium to help cadets understand how the equipment works. Wind direction indicators are used as a navigation tool for pilots to determine landing direction on airport runways. This study was conducted at the Palembang Aviation Polytechnic using mixed methods, namely research and development and quantitative. The object of the research is cadets of the airport engineering technology study program.  Determining whether there are differences in the results or not, by using paired t test. The study results show that the cadets are very enthusiastic in learning and developing these tools, as well as increasing their knowledge and competence in the field of visual landing aids at airports. With this learning media, cadets can better understand how it works. By increasing the competency of cadets, it is hoped that it can support aviation safety in Indonesia.